Impact assessment of national and regional policies using the Philippine Regional General Equilibrium Model - Briones, Roehlano M. (The Philippine Review of Economics, 2015)
For the Philippines, a quantitative analysis is more useful for policy if it incorporates regional differences in welfare and economic structure. However, owing to the absence of key regional data, existing computable general equilibrium (cge) models offer limited analysis of regional effects or national impacts of region-specific interventions. This study formulates a regional (cge) model that overcomes these limitations. The applications of the model showed the following: (1) completion of the tariff reform program in agriculture will contract some import-competing sectors in lagging regions, but will improve welfare across all regions; (2) productivity growth in agriculture can more than offset these contractionary effects; (3) investments in marketing infrastructure promise significant pay-offs, though with a trade-off between the size and spread of welfare gains across regions; and (4) combining trade reform with marketing infrastructure investments slightly mitigates some of the contractionary effects from the former.